Ativação ultrassônica do ácido fosfórico e do álcool na remoção do hidróxido de cálcio intracanal: um estudo confocal do terço apical - FERNANDES, Adriany Dias (2018)
Calcium hydroxide is not easily removed from the root canal and its residues can affect the quality of endodontic obturation. The most commonly used protocols for its removal do not show satisfactory results. The ultrasonic activation allows the agitation and the cavitation of the irrigating solution favoring the cleaning of the root canal. This study evaluates the removal of calcium hydroxide from the perimeter of the root canal and the dentinal tubules of the apical third of human teeth extracted by confocal microscopy. 40 palatal roots of human upper first molars were submitted to biomechanical preparation with the ProTaper system and insertion of intracanal calcium hydroxide and propylene glycol medication, associated with 0.1% Rhodamine B. The specimens were stored at 37ºC for 7 days and divided into groups according to the protocol used to clean the root canal: G1 - 6 mL NaOCL 2.5% with three shafts of 20 seconds each; G2 - 6 mL EDTA-T 17% with three shakes of 20 seconds each; G3 - 6 mL phosphoric acid 37% with three shakes of 10 seconds each; G4 - 6 mL ethyl alcohol 70% with three shakes of 20 seconds each; and control group, where the medication was not removed. mages of confocal microscopy 2 mm below the apical foramen were obtained in order to compare the cleaning in the perimeter of the root canal and the depth of cleaning of the dentinal tubules provided by each group. Statistical tests of Kruskal-Wallis and Dunn post-test were used, at a significance level of 5%. The results of this work show that solutions of phosphoric acid 37% and alcohol 70% were more efficient in the removal of this medication from the perimeter of the root canal. Furthermore, in the perimeter cleaning analysis, it was observed that ethyl alcohol 70% showed a better performance than the EDTA-T a 17%. The other groups did not present a statistically significant difference. In relation to the depth of penetration, ethyl alcohol 70% presented better results in relation to the control. The other groups did not present a statistically significant difference.